2013
DOI: 10.2215/cjn.06330612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spironolactone and Amiloride on Thiazolidinedione-Induced Fluid Retention in South Indian Patients with Type 2 Diabetes

Abstract: SummaryBackground and objectives Thiazolidinediones (pioglitazone and rosiglitazone) induce renal epithelial sodium channel (ENaC)-mediated sodium reabsorption, resulting in plasma volume (PV) expansion. Incidence and long-term management of fluid retention induced by thiazolidinediones remain unclear.Design, setting, participants, & measurements In a 4-week run-in period, rosiglitazone, 4 mg twice daily, was added to a background anti-diabetic therapy in 260 South Indian patients with type 2 diabetes mellitus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…A role for ENaC in CNT in TZD-induced fluid retention dovetails with the physiological relevance of ENaC in this segment for Na + reabsorption [17-20]. The findings are also in agreement with studies that found that the ENaC blocker, amiloride, and the aldosterone-antagonist, spironolactone, attenuated TZD-induced fluid retention in diabetic patients [16;23]. …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A role for ENaC in CNT in TZD-induced fluid retention dovetails with the physiological relevance of ENaC in this segment for Na + reabsorption [17-20]. The findings are also in agreement with studies that found that the ENaC blocker, amiloride, and the aldosterone-antagonist, spironolactone, attenuated TZD-induced fluid retention in diabetic patients [16;23]. …”
Section: Discussionsupporting
confidence: 83%
“…The epithelial sodium channel ENaC is expressed in the apical membrane of the CNT and CD and serves as a primary effector of regulated sodium reabsorption. Studies in mice [15] and in patients with type 2 diabetes [16] found that TZD-induced weight gain and fluid retention were attenuated by the ENaC inhibitor, amiloride, indicating a potential role of ENaC in this process.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows the characteristics of the 18 selected trials; 13 were in both men and women, showing no effect or a potential benefit. Eight trials were in people with diabetes, of these 8 trials, 6 were conducted in people with type 2 diabetes (212 in the treatment arms and 207 in the placebo arms) [11,[26][27][28][29][30]. One cross-over trial was conducted in 21 people with type 1 diabetes [31].…”
mentioning
confidence: 99%
“…The changes in Hct have been used as a surrogate marker for TZD-induced plasma volume expansion. Viswanathan et al (27) recently showed that of 260 patients on RGZ, 70% had plasma volume expansion as reflected by a drop of Hct. The severity of the side effect increases in patients treated with TZD in combination with insulin therapy (15).…”
mentioning
confidence: 99%